2022
DOI: 10.1136/jclinpath-2022-208152
|View full text |Cite
|
Sign up to set email alerts
|

Novel histological repertoire of crypt-associated anomalies in inflamed colon mucosa

Abstract: AimsStudying crypt branching in ulcerative colitis (UC) and in infectious colitis (IC), we detected previously unreported crypt-associated anomalies (CAAs). The objective was to describe, illustrate and assess the frequency of CAAs in inflamed colon mucosa in patients with UC and IC.MethodsSections from 100 consecutive biopsies with UC, in 50 with IC and in 27 with UC in remission (UCR) were reviewed. The following CAAs were identified: crypt eosinophilia, intracryptal epithelial hyperplasia, intracryptal epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Specific histologic features were also assessed as markers of disease or as predictors of response to therapy among IBD patients. For example, extensive crypt eosinophilia and intracryptal epithelial budding can differentiate UC from infectious colitis (15), and the proportion of plasma cells in the lamina propria was found as a robust pretreatment biomarker of response to anti‐tumor necrosis factor‐α therapy (16).…”
Section: Discussionmentioning
confidence: 99%
“…Specific histologic features were also assessed as markers of disease or as predictors of response to therapy among IBD patients. For example, extensive crypt eosinophilia and intracryptal epithelial budding can differentiate UC from infectious colitis (15), and the proportion of plasma cells in the lamina propria was found as a robust pretreatment biomarker of response to anti‐tumor necrosis factor‐α therapy (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the same group demonstrated that specimen orientation could represent a bias in crypt morphology evaluation; a significant portion of the histologic section that resulted in a diagnosis of IBD held cross-cut crypts, an inappropriate sectioning plane that modifies the correct assessment of the other histological parameters that defined the diagnosis of IBD [19][20][21]. On the other side, a series of cryptassociated anomalies were described in addition to crypt branching in crypt destructive inflammations that should be considered in their assessment on histologic slides [22]. These new acquisitions could contribute to the construction of more objective criteria for the differential diagnosis between crypt destructive and nondestructive colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Це дає можливість експериментально моделювати специфічні ураження травної системи та екстрапо-Актуальні проблеми сучасної медицини лювати результати на людину [10]. Важливим критерієм оцінки функцій кишкового травлення і всмоктування є глибина крипт слизової оболонки кишечника [11], кількість крипт, їх структура та інтенсивність клітинної інфільтрації [12] .…”
Section: вступunclassified